2012 25th International Symposium on Discharges and Electrical Insulation in Vacuum (ISDEIV) 2012
DOI: 10.1109/deiv.2012.6412524
|View full text |Cite
|
Sign up to set email alerts
|

Method of determination of the electron density in the gap of high-current vacuum arc on the base of continual radiation analysis

Abstract: In our previous work is shown that in the visual spectral region of radiation of the high-current vacuum arc with copper electrodes there is a spectral "window" that allows to register continuum radiation (including at high-current densities). This fact was used for elaboration of the method of determination of the electron density in the gap of high-current vacuum arc. The method was verified by comparison of the obtained results with known results received by different methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Such an increase in the electron density proportion with increasing t showed that the dominant component in a vacuum plasma gradually became electrons in the process of arc extinction. The orders of the observed electron densities in this paper were in good agreement with the experimental data for the vacuum arcs with similar current densities determined using a spectroscopic method [5].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Such an increase in the electron density proportion with increasing t showed that the dominant component in a vacuum plasma gradually became electrons in the process of arc extinction. The orders of the observed electron densities in this paper were in good agreement with the experimental data for the vacuum arcs with similar current densities determined using a spectroscopic method [5].…”
Section: Resultssupporting
confidence: 87%
“…Localised electron and metal vapour densities in vacuum arcs have been measured mainly by optical emission spectroscopy [4,5] and interferometry [6][7][8]. However, general vacuum arc discharges have poorly reproducible discharge paths.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the application of high-current vacuum arcs in switching devices, mainly for medium voltages, gives reason to enhanced investigations [1]. Although optical investigations are among the standard experimental methods for the analysis of high-current vacuum arcs, few publications can be found that deal with their spectroscopy [2]- [7]. Nevertheless, optical emission spectroscopy gives us the opportunity to gain information on plasma parameters like ionization degree, temperature, and partial pressure.…”
Section: Introductionmentioning
confidence: 97%